2009
DOI: 10.1002/jrs.2535
|View full text |Cite
|
Sign up to set email alerts
|

Crystal → nematic phase transition in the liquid crystalline system 1‐isothiocyanato‐4‐(trans‐4‐propylcyclohexyl) benzene (3CHBT) probed by temperature‐dependent micro‐Raman study and DFT calculations

Abstract: Raman spectra of 3CHBT in unoriented form were recorded at 14 different temperature measurements in the range 25-55 • C, which covers the crystal → nematic (N) phase transition, and the Raman signatures of the phase transition were identified. The wavenumber shifts and linewidth changes of Raman marker bands with varying temperature were determined. The assignments of important vibrational modes of 3CHBT were also made using the experimentally observed Raman and infrared spectra, calculated wavenumbers, and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Vikram et al . described the crystal nematic phase transition of the liquid crystalline1‐isothiocyanato‐4‐(trans‐4‐propylcyclohexyl) benzene (3CHBT) system as probed by temperature‐dependent micro‐Raman and DFT calculations . Raman scattering and IR absorption of ammonium oxyfluoride crystals (NH 4 ) 3 WO 3 F 3 , (NH 4 ) 2 KWO 3 F 3 and Cs 2 (NH 4 )WO 3 F 3 were compared by Vtyurin et al .…”
Section: Solid‐state Studiesmentioning
confidence: 99%
“…Vikram et al . described the crystal nematic phase transition of the liquid crystalline1‐isothiocyanato‐4‐(trans‐4‐propylcyclohexyl) benzene (3CHBT) system as probed by temperature‐dependent micro‐Raman and DFT calculations . Raman scattering and IR absorption of ammonium oxyfluoride crystals (NH 4 ) 3 WO 3 F 3 , (NH 4 ) 2 KWO 3 F 3 and Cs 2 (NH 4 )WO 3 F 3 were compared by Vtyurin et al .…”
Section: Solid‐state Studiesmentioning
confidence: 99%
“…At molecular level rotation of spacers in the mesogenic molecules, charge transfer phenomenon, changes in intra/intermolecular H‐bonding interactions, changes in molecular symmetry and others are observed during phase transitions, and therefore for better understanding, molecular techniques are needed. In LC systems due to the anisotropy of the molecular polarizability, Raman spectroscopy has a great potential to reflect the molecular changes during phase transitions in terms of some measurable parameters of marker bands . XRD, density functional theoretical (DFT) and Raman spectroscopic techniques together can be very helpful to study phase transitions at molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, [6] we have discussed the molecular dynamics of the crystal → nematic and nematic → isotropic transitions in 3CHBT. To the best of our knowledge, low temperature Raman study of nCHBT series is not reported as yet.…”
Section: Introductionmentioning
confidence: 99%